In vitro reconstitution of the coenzyme A biosynthesis pathway for the study of its regulation and disruption by possible inhibitors - Mostert, Konrad Johannes (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.